Membangun Karakter Siswa Sekolah Dasar Melalui Gelar Karya: Sebuah Pendekatan Inovatif - Nurlaila, Evi; Margaretha Sinaga, Risma (EDU AKOMMEDIA : JURNAL ILMU PENDIDIKAN, 2025)
This study aims to describe the strengthening of character education through elementary school students' work titles. Student work titles in elementary schools can be an effective means to strengthen character education. Work titles are not just a place to show off learning outcomes, but also a platform to foster positive character values ​​in students through the process of preparation, implementation, and evaluation of activities. The research method used is qualitative descriptive with the research subjects of school residents at SDN 2 Sawah Brebes, Bandar Lampung City. The results of the study showed that strengthening character education through student work titles at SDN 2 Sawah Brebes contains the character values ​​of hard work, responsibility, creativity, cooperation, self-confidence, discipline, honesty, and independence. In addition, through work titles, there are also goals and benefits for elementary school students to train their physical, mental, intellectual, emotional and also their potential, interests and talents. For this reason, this work title is one of the annual routine agendas carried out by the school. Given the very large positive impact on students, this work title can be an example and its practice can be imitated by other schools. So that the good impact of strengthening character education through elementary school students' work titles can reach a wider audience. Proper implementation, the work title can be an integral part of the learning process and help shape a young generation with character.